Informal animation sketching: Requirements and design - DAVIS, Richard C. (Institutional Knowledge at Singapore Management University, 2004)
We present an interface design for creating informal animations from sketches. Current tools for creating animation are extremely complex. This makes it difficult for designers to prototype animations and nearly impossible for novices to create them at all. Simple animation systems exist but severely restrict the types of motion that can be represented. To guide our design of an animation sketching interface, we conducted field studies into the needs of professional and novice animators. These studies show the wide variety of motions that users desire in informal animations and indicate how to prioritize these types of otion. The interface described here allows the most important types of motion to be defined with pen gestures, and gives visual feedback for coordination of events.